Dental Infection and Pregnancy: the Lack of Treatment by the Dental Professional Evolving to a Complex Maxillofacial Infection - Pereira, Rodrigo Dos Santos; Gomes-Ferreira, Pedro Henrique Silva; Bonardi, João Paulo; Silva, Jonathan Ribeiro da; Latini, Gustavo Lima; Hochuli-Vieira, Eduardo (Wolters Kluwer, 2017)
Infections of the maxillofacial complex caused by caries disease are common in dental practice. The professionals have to have technical knowledge to treat it at the onset of the condition and avoid the spread to deep anatomical spaces of face and neck, which can implicate in a risk of patients' life.In Brazil, current dental professionals usually denied oral surgical treatments in patients with some clinical conditions, not because of fear to resolve it but for lack of knowledge to treat it. An example of these conditionals is pregnancy. It is well known that during the pregnancy period, the patient can be treated in the correct period of gestation. Early diagnosis is crucial for effective therapy in serious infections. The treatment has to be crucial during pregnancy because of the potentially fatal situation that the disease can create to the pregnant woman and the fetus.The aim of this article is to demonstrate a case of dental caries in a pregnant patient, which was evaluated by other professionals and had the treatment denied, evolving to a serious maxillofacial infection.